Pelatihan Penggunaan Aplikasi Accurate Untuk Pengajar Pada Yayasan Perguruan Sultan Iskandar Muda - Hita Hita; Djoni Djoni; Culita Culita; Mbayak Ginting (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
A teacher's ability and knowledge have a big impact on students. So teachers also need various training to improve their ability to provide effective teaching. The aim of this training is to provide teachers with the opportunity to understand and master the use of Accurate in supporting accounting learning. So it can improve teachers' abilities in teaching the use of the Accurate application simultaneously with accounting learning. The methods used in this training are initial evaluation (pre-test), presentation of material, training in application use, and final evaluation (post-test). Based on the results of the pre-test and post-test training, it can be concluded that there has been an increase in the grades and average grades of the teachers. This shows that the training that has been carried out has been successful in increasing the knowledge and skills of teachers in understanding the use of features and tools in the Accurate application.